Algebra 1A

posted by .

Help Please! multiply 5/7(-35)= 0 is this correct? if not will you show me please? thanks

  • Algebra 1A -

    No.

    5/7 * 35/1 = 135/7 = 25

  • Algebra 1A -

    5/7(-35) is not = 0
    You have no unknown to solve.

  • Algebra 1A - Correction -

    I forgot the minus sign.

    5/7(-35) = -25

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    x/2=3y/5 can you show me how you got the answer please y=3/4x-2 I don't think it is correct. Starting over To solve for y first multiply both sides by 5 (5)x/2=3y/5 (5) Cancel 5 on right side to get 5x/2=3y Now multiply both sides …
  2. Math(Please respond)

    .50 - x / x = 3.20e-1 I need to solve for x. I was going to do .50 X 3.20e-1 and then take the square root but this is not correct. I am not sure what to do. Thank you for your help. Math(Please help) - Reiny, Tuesday, April 17, 2012 …
  3. Chemistry(Please check)

    .50 - x / x = 3.20e-1 I need to solve for x. I was going to do .50 X 3.20e-1 and then take the square root but this is not correct. I am not sure what to do. Thank you for your help. Math(Please help) - Reiny, Tuesday, April 17, 2012 …
  4. math algebra

    multiply and simplify (4-z)z =4z-zsquare?
  5. Math, Please Help!

    Ned divided a given number by 3 and then added 2. If he should have multiplied the number by 3 and then subtracted 2, which of the following two steps can he do next to get the correct answer?
  6. Algebra 2

    More About Complex Numbers Multiply (4+3i)(1-i) Please show work i need help
  7. Algebra 2

    More About Complex Numbers Multiply (4+3i)(1-i) Please show work i need help
  8. algebra

    Multiply. (x+4)(x-2) = x^2+2x-8 Is the answer correct, if not can you please point out what I did wrong?
  9. algebra

    Multiply and simplify. Assume that no radicands were formed by raising negative numbers to even powers. √6x^3 * √18x^2 = √2 * 3 * x^3 * √2 * 3^2 * x^2 = √2 * 3x^2x * √2 * 3^2 * x^2 = 6x^2 * √3x …
  10. algebra

    Multiply and simplify. Assume that no radicands were formed by raising negative numbers to even powers. √6x^3 * √18x^2 = √2 * 3 * x^3 * √2 * 3^2 * x^2 = √2 * 3x^2x * √2 * 3^2 * x^2 = 6x^2 * √3x …

More Similar Questions